2019
DOI: 10.1088/2399-6528/ab5bb7
|View full text |Cite
|
Sign up to set email alerts
|

Conjecture of new inequalities for some selected thermophysical properties values

Abstract: In 2005 it was rigorously shown with string theory methods that there is a lower bound for the ratio of the shear viscosity η and the volume density of entropy s=S/V given byHere we extend this result in a heuristic manner to other ratios of thermophysical properties. We conjectured that there are rigorous non-zero lower bounds for the Lorenz number L as well as other combinations of equilibrium and transport properties. We suggest that the lower bounds and the corresponding inequalities can be written in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 109 publications
(147 reference statements)
1
1
0
Order By: Relevance
“…A similar relation was deduced by Falasco and Esposito [176] and verified experimentally by Yan et al [177]. Many additional indeterminacy relations exist; a comprehensive list is given by Hohm [174]. All these indeterminacy relations suggest that entropy resembles action, with a multiple O(1) k of the Boltzmann constant playing a role similar to that of h. For example, Parker et al [178,179] use similar versions of the entropic uncertainty relations and the quantum of entropy to calculate the configurations of alpha particles and details of cosmological systems.…”
Section: Indeterminacy Relationssupporting
confidence: 70%
See 1 more Smart Citation
“…A similar relation was deduced by Falasco and Esposito [176] and verified experimentally by Yan et al [177]. Many additional indeterminacy relations exist; a comprehensive list is given by Hohm [174]. All these indeterminacy relations suggest that entropy resembles action, with a multiple O(1) k of the Boltzmann constant playing a role similar to that of h. For example, Parker et al [178,179] use similar versions of the entropic uncertainty relations and the quantum of entropy to calculate the configurations of alpha particles and details of cosmological systems.…”
Section: Indeterminacy Relationssupporting
confidence: 70%
“…In 2004, Kovtun, Son, and Starinets showed that the ratio between shear viscosity η and entropy volume density s follow [173,174]…”
Section: Indeterminacy Relationsmentioning
confidence: 99%